Dual lysine and N-terminal acetyltransferases reveal the complexity underpinning protein acetylation - Bienvenut, Willy V.; Brünje, Annika; Boyer, Jean-Baptiste; Mühlenbeck, Jens S; Bernal, Gautier; Lassowskat, Ines; Dian, Cyril; Linster, Eric; Trinh, Dinh-Van; Konert, Minna; Jung, Vincent; Seidel, Julian; et al. (Molecular systems biology, 2020)
Abstract Protein acetylation is a highly frequent protein modification. However, comparatively little is known about its enzymatic machinery. N-α-acetylation (NTA) and ε-lysine acetylation (KA) are known to be catalyzed by distinct families of enzymes (NATs and KATs, respectively), although the possibility that the same GCN5-related N-acetyltransferase (GNAT) can perform both functions has been debated. Here, we discovered a new family of plastid-localized GNATs, which possess a dual specificity. All characterized GNAT family members display a number of unique features. Quantitative mass spectrometry analyses revealed that these enzymes exhibit both distinct KA and relaxed NTA specificities. Furthermore, inactivation of GNAT2 leads to significant NTA or KA decreases of several plastid proteins, while proteins of other compartments were unaffected. The data indicate that these enzymes have specific protein targets and likely display partly redundant selectivity, increasing the robustness of the acetylation process in vivo. In summary, this study revealed a new layer of complexity in the machinery controlling this prevalent modification and suggests that other eukaryotic GNATs may also possess these previously underappreciated broader enzymatic activities.
Gesehen am 13.10.2020